2020
DOI: 10.4236/ojpp.2020.104039
|View full text |Cite
|
Sign up to set email alerts
|

“Dual State”, “Double-Perspective” and “Cartesian-Like Dualism” Are Three Forms of Dualisms Emerging in Mind Like in a Matrioska

Abstract: After a long time, people are still debating over "Cartesian-like Dualism" (CLD), i.e. towards the separation of "res-extensa" from "res-cogitans". Since we suspect that this is due to a general attraction of mind towards the darkness of metaphysics, we have investigated the mental origin of this attraction. In human mind, we can envisage three different functional levels emerging one from the other like in a Matrioska; the three levels cause the arousal of as many forms of "dualisms": 1) The 1 st-level corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In the philosophy of mind, this dualism was so beloved by many philosophers, since Plato up until now; in the attempt of discovering the truth, we analysed the mechanism of its ontology in CM. We concluded that the binomial Ego-FW is an illusion installed in CM that apparently causes a mess of false information, e. g. the belief of deciding actions independently, at will [17]. In summary, we have seen that the representation in the mind of the outer world is flawed and virtual.…”
Section: Introductionmentioning
confidence: 79%
“…In the philosophy of mind, this dualism was so beloved by many philosophers, since Plato up until now; in the attempt of discovering the truth, we analysed the mechanism of its ontology in CM. We concluded that the binomial Ego-FW is an illusion installed in CM that apparently causes a mess of false information, e. g. the belief of deciding actions independently, at will [17]. In summary, we have seen that the representation in the mind of the outer world is flawed and virtual.…”
Section: Introductionmentioning
confidence: 79%